Deficits of Calf Muscles Strength and Rate of Force Development After Achilles Tendon Rupture - Aleknavičiūtė-Ablonskė, Vaida; Savenkovienė, Agnė; Skurvydas, Albertas (Social Welfare: Interdisciplinary Approach, 2018)
Many studies, investigating biomechanical properties of plantar flexors muscle-tendon unit after ATR surgery, reported an incomplete calf muscle contractile functional recovery. However, these studies only investigated the plantar flexors muscle function failing to provide information about the adaptive changes in motor strategy. In fact, the development of adaptive changes in motor strategies, due to both mechanical and neural factors, may result in pathological musculoskeletal conditions over the long term. Understanding physiological calf muscle changes due to long-term immobilization may help prevent Achilles tendon re-rupture cases.